Landrace Swine Mortality Due to Colibacillosis in Conventional Farming - Yasa, Gede Sastra Darma; Tono PG, I Ketut; Winaya, Ida Bagus Oka; Apsari, Ida Ayu Pasti; Sari, Tri Komala (Universitas Airlangga, 2025)
Background: Colibacillosis, caused by Escherichia coli infection, is a major health issue in pig farming, leading to high morbidity and mortality rates. This report describes a case that occurred on a conventional pig farm in Puhu Village, Gianyar District, Bali. Purpose: This study aimed to determine the cause of death in a 43 day old Landrace pig exhibiting clinical signs including brown watery diarrhea, dehydration, and weight loss. Case(s): A necropsy was conducted at the Veterinary Pathology Laboratory, Faculty of Veterinary Medicine, Udayana University. Bacteriological examination was performed by culturing organ samples on Nutrient Agar and Eosin Methylene Blue Agar, followed by biochemical testing using Triple Sugar Iron Agar and Sulfide Indole Motility media, among others. Parasitological examination was carried out using the fecal float concentration method. Case Management: Epidemiological assessment revealed morbidity, mortality, and case fatality rates of 1.89%, 0.63%, and 33.33%, respectively. Gross pathological findings included intestinal and gastric dilation and hemorrhage, intestinal edema, and lesions in the brain, trachea, lungs, heart, liver, and kidneys. Histopathological examination revealed localized intestinal congestion, generalized cardiac congestion, and inflammatory cell infiltration in the intestinal mucosa. Bacteriological analysis confirmed Escherichia coli with alpha-hemolytic activity on blood agar. Eimeria spp. oocysts were not detected in the fecal samples. Conclusion: The pig’s death was attributed to colibacillosis caused by Escherichia coli infection. This case highlights the importance of early detection, strict biosecurity measures, and proper sanitation practices to prevent disease outbreaks in conventional pig farming.